2015
DOI: 10.1021/acschembio.5b00501
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Glycoengineering Using an Unnatural Sialic Acid for the Detection of Sialoglycan Biosynthesis Defects and On-Cell Synthesis of Siglec Ligands

Abstract: Sialoglycans play a vital role in physiology, and aberrant sialoglycan expression is associated with a broad spectrum of diseases. Since biosynthesis of sialoglycans is only partially regulated at the genetic level, chemical tools are crucial to study their function. Here, we report the development of propargyloxycarbonyl sialic acid (Ac5NeuNPoc) as a powerful tool for sialic acid glycoengineering. Ac5NeuNPoc showed strongly increased labeling efficiency and exhibited less toxicity compared to those of widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 53 publications
5
44
0
1
Order By: Relevance
“…Together, the direct inhibition of sialyltransferases and the indirect inhibition of sialic acid synthesis result in metabolic sialic acid blockade in the cell (Figure 1a). Previously, we have reported that Ac 5 3F ax Neu5Ac blocks sialic acid incorporation into surface glycans of the monocytic THP‐1 cell line 19 . Here we assessed if the sialic acid mimetic blocks sialoglycan expression in freshly generated moDCs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Together, the direct inhibition of sialyltransferases and the indirect inhibition of sialic acid synthesis result in metabolic sialic acid blockade in the cell (Figure 1a). Previously, we have reported that Ac 5 3F ax Neu5Ac blocks sialic acid incorporation into surface glycans of the monocytic THP‐1 cell line 19 . Here we assessed if the sialic acid mimetic blocks sialoglycan expression in freshly generated moDCs.…”
Section: Resultsmentioning
confidence: 95%
“…We have previously shown that a fluorinated sialic acid mimetic, Ac 5 3F ax Neu5Ac, blocks sialic acid expression in human and mouse tumor cell lines with high efficiency and specificity 15 , 19 , 20 , 21 . Most notably, this inhibitor caused a prolonged inhibition of the sialic acid biosynthesis (about 48 h to recover 50% sialylation) and is chemically pure and free from endotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Both sialic acid analogues are well-tolerated by the cellular sialylation pathway, and these small modifications to the C-5 position are generally thought to be nonintrusive. There is evidence, however, that the modification of sialic acids at the C-5 position affects their recognition and cleavage by bacterial neuraminidases.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our previously published comparison of Ac 5 SiaNAz and Ac 5 SiaNPoc (see ref (9)), the click reaction was now done at 37 °C instead of at room temperature, which greatly increased the fluorescence signal and gave usual click efficiencies of 80% or higher (see ref (10)).…”
mentioning
confidence: 96%
“…Es wurde gezeigt, dass durch den Gebrauch von N ‐Propargylcarbonylmannosamin (ManNProc) oder N ‐Propargylcarbonylsialinsäure (Neu5Proc) Zellen kreiert werden können, die hoch‐affine Liganden für Siglecs exprimieren (High‐affinity siglec ligand‐expressing cells, HASLECs) . In dieser Studie wurden die vorbehandelten, Neu5Proc tragenden Zellen über CuAAC mit bestimmten Azid‐Gruppen verbunden, welche die Bindungsaffinität zu spezifischen Siglec‐Subtypen stark erhöhen .…”
Section: Anwendungsbeispiele Für Nichtnatürliche Sialinsäuren Mit Biunclassified